Strategi dan Tantangan Pengelolaan Usaha Offline dan Affiliate: (Studi Kasus pada Rio Ponsel di Tambak Bayan) - Nuraisah Nuraisah; Syafira Okta Vionna Wirya; Zainarti Zainarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Business management based on the application of a combination of offline and online is inseparable from various challenges that can arise, especially in terms of HR management itself, namely the business owner. So that the right strategic action is needed so that the business can run well. This study aims to get an idea of ​​​​how the strategy is, and what challenges are faced in managing a business based on a combination of offline and digital affiliates at Rio Ponsel. This study uses a qualitative approach with a case study method and data collection through interviews with Rio Ponsel business actors. The results of the study showed that the business management strategy that combines offline sales systems and marketing through the TikTok affiliate program at Rio Ponsel is in the form of implementing internal strategies such as product development according to local market needs, implementing positive personal branding, and improving service quality directly. In addition, external strategies are also applied. Meanwhile, the biggest challenge faced by Rio Ponsel business actors is the high level of competition with competitors both in the offline and digital markets.